Hypertrophic osteoarthropathy, spider naevi and oestrogen hyperexcretion associated with adenocarcinoma. Issue 719 (September 1985) - Brear, S. G.; Edwards, J. D.; Rademaker, M.; Doyle, L.
Abstract : We describe two patients with hypertrophic osteoarthropathy, spider naevi and elevated 24 h urinary oestrogen excretion associated with an adenocarcinoma. In one of the patients, the spider naevi and the clinical signs of hypertrophic osteoarthropathy disappeared and the 24 h urinary oestrogen returned to normal following removal of the tumour.